Pengaruh Pemberian Jus Sirsak Terhadap Kadar Asam Urat di Kelurahan Paudean Kecamatan Lembeh Selatan - Nurfitriyana B. Utiarahman; Agust A. Laya; Kristine Dareda (STIKES Columbia Asia Medan, 2023)
Uric acid or gout is a condition with symptoms of unbearable pain, swelling and heat in the joint area. This disease is easier to attack men, especially those over the age of 30 years, and in women will appear after menopause. The purpose of this study was to determine the effectiveness of giving soursop juice on uric acid levels in Paudean Village, South Lembeh District. This research uses Quasy- Experiment and applies the design of One Group Pre-Post Test Design. The sampling technique is using Purposive Sampling. With total 12 people as a sampling who had previously checked uric acid levels, after that the data collected had been tested for normality. The hypothesis was tested with the Paired T-Test to determine the Gout decreases in subject with a meaning level (α) of 0.05. The results showed the most gender categories obtained in the study was men with 7 subject (58.3%), women 5 subject ts (41.7%). And the category of age was most at 56-65 years, with 7 subject (58.4%). As well as many jobs categories from the suffer from gout, namely IRT (house wife). The conclusion in this study giving soursop juice is effected on decrease the uric acid levels. Be expected for the uric acid sufferers to consumption soursop juice and also apply how to make soursop juice.